Anti-chain based algorithms for timed/probabilistic refinement checking - Wang, Ting (2020)
Refinement checking answers the question on whether an implementation model is a refinement of a specification model, which is of great value for system verification. Some refinement relationships, e.g., trace refinement and failures/divergence refinement, have been recognized for different verification purposes. In general, refinement checking algorithms often rely on subset construction, which incurs in the state space explosion problem. Recently the anti-chain based approach has been suggested for trace refinement checking, and the results show a significant improvement. In this paper, we investigate the problems of applying the anti-chain approach to timed refinement checking (a timed implementation vs. a timed or untimed specification) and probabilistic refinement checking (a probabilistic implementation vs. a non-probabilistic specification), and show that the state space can be reduced considerably by employing the anti-chain approach. All the algorithms have been integrated into the model checking tool PAT, and the experiments have been conducted to show the efficiency of the application of anti-chains.